UMP’s 5th Convocation 1,030 students received their degrees and diplomas - UMP, PNC
Menteri Besar of Pahang, Dato’ Sri Haji Adnan Haji Yaakob was awarded the honorary doctorate for technology management from Universiti Malaysia (UMP) Pahang Chancellor, Tengku Mahkota of Pahang Tengku Abdullah Sultan Ahmad Shah in conjunction with its 5th Convocation at the sports complex hall on October 9, 2010.